Water column raw data (Kongsberg EM710 entire dataset) of RV METEOR during cruise M193 - Thomas Lüdmann; Hildegard Westphal; Fabio Marchese; Giorgio Castellan; Manuel Eduardo Ariza Fuentes; Silvia Vicario; Mia Schumacher (PANGAEA, 2025)
Raw water column data were collected aboard RV METEOR during cruise M193 using a Kongsberg EM 710 multibeam echosounder. The expedition took place during 08.09.2023 – 06.10.2023 from Limassol (Cyprus) - Jeddah (Saudi Arabia) in the Mediterranean and Red Sea. The major aims of M193 were to investigate whether and how Pleistocene humidity-aridity phases are recorded in marine sediments; how these periods affected the development of shallow- and deep-water carbonate systems along offshore western Saudi Arabia; and where unique warm-water (>20°C) high-salinity deep-sea corals assemblages with an unclear taxonomy thrive. Data were recorded in the EEZ of Saudi Arabia. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data acquisition was done by the Institute of Geology, University of Hamburg, provision of the data is supported by the DAM Underway Project and published according to the FAIR principles.